Studi Pendahuluan Hematologis Ayam Arab Pada Berbagai Tingkat Umur dan Jenis Kelamin - Tethool, Angelina N.; Murwanto, Agustinus Gatot; Dwiranti, Febriza Dwiranti (Fakultas Peternakan Universitas Papua, 2006)
Hematologist (coagulation, hemoglobin, sedimentation rate and haematocrit) is a parameter to know Arab chicken's physiology condition. Unfortunately there is however lack information of hematologist Arab chicken available in a farm which the chicken is raising. Twenty Arab chickens which different ages ( 5 months, 7 months and 1.5 years) and different sex (female and male) is used as samples. Blood samples is taken from vena cava in left and right wings. Results of the present study showed that the chicken is healthy, even though the hematocrit is different with literature. The differences is expe,,1.ed by the chicken which used in experiment different with the chicken in the literature.